2017
DOI: 10.3389/fendo.2017.00129
|View full text |Cite
|
Sign up to set email alerts
|

Increased Short-Term Beat-to-Beat QT Interval Variability in Patients with Impaired Glucose Tolerance

Abstract: Prediabetic states and diabetes are important risk factors for cardiovascular morbidity and mortality. Determination of short-term QT interval variability (STVQT) is a non-invasive method for assessment of proarrhythmic risk. The aim of the study was to evaluate the STVQT in patients with impaired glucose tolerance (IGT). 18 IGT patients [age: 63 ± 11 years, body mass index (BMI): 31 ± 6 kg/m2, fasting glucose: 6.0 ± 0.4 mmol/l, 120 min postload glucose: 9.0 ± 1.0 mmol/l, hemoglobin A1c (HbA1c): 5.9 ± 0.4%; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
4
11
0
1
Order By: Relevance
“…The mean ± SD of QTc did not differ significantly between two groups. This finding is consistent with results of Orosz A and Stern K researches which found that the QT interval in DM and pre-DM individuals was no longer than normal individuals [23,24]. However, other researchers have found different results.…”
Section: Long Qt and Cansupporting
confidence: 92%
“…The mean ± SD of QTc did not differ significantly between two groups. This finding is consistent with results of Orosz A and Stern K researches which found that the QT interval in DM and pre-DM individuals was no longer than normal individuals [23,24]. However, other researchers have found different results.…”
Section: Long Qt and Cansupporting
confidence: 92%
“…First in the chronic AV-block dog model, then in other animal experimental proarrhythmia models (Thomsen et al, 2004;Lengyel et al, 2007a;Jacobson et al, 2011) and in clinical settings (Hinterseer et al, 2008;Hinterseer et al, 2009;Hinterseer et al, 2010;Oosterhoff et al, 2010), it has been repeatedly shown that STV QT has a higher predictive value for proarrhythmia risk than the overall prolongation of repolarization (QT duration). STV QT has been used in several studies to confirm the safety of different drugs (Oros et al, 2006;Antoons et al, 2010;Varkevisser et al, 2012), to characterize pro-arrhythmic drug effects (Thomsen et al, 2004;Thomsen et al, 2006b;Kristof et al, 2012), and to assess temporal repolarization instability in patients with co-morbidities associated with repolarization disturbances (Orosz et al, 2015a;Orosz et al, 2015b;Orosz et al, 2017).…”
Section: Proarrhythmia Ecg Markers For Temporal Instability Of Repolamentioning
confidence: 99%
“…[ 29 ] Recently, a significant correlation was shown between elevated STV-QT and parameters of sympathetic predominance in patients with impaired glucose tolerance. [ 30 ] A study by Piccirillo et al found a positive relation between the level of anxiety and a high QTVI. [ 31 ] On the other hand, QT variability was significantly reduced after administration of metoprolol or carvedilol compared to placebo in patients with ischemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%